Digital British Islam - Digital British Islam: How do Cyber Islamic Environments Impact Everyday Life? (2023)
"‘Digital British Islam: How do Cyber Islamic Environments impact everyday life?’’ (shortened to ‘DBI’) is an innovative multi-institution investigation led by Professor Gary R. Bunt (University of Wales Trinity Saint David – UWTSD). The ESRC awarded DBI a £804,000 grant. The three-year project began in 2022"